Refinement Engineering Properties of Clay Soils By Adding Cement And Ceramic Dust of Al-Dair Area, Northwest of Basrah (Iraqi National Journal of Earth Science (INJES), 2026)
This study investigates the effect of adding construction waste, specifically ceramic dust and cement, on the geotechnical properties of clay soils in Al-Dair area, located in the northwestern part of Basrah Governorate, southern Iraq. This study focuses on solving various problems that the soil suffers from, such as swelling and shrinkage, which generate pressures on shallow foundations, including collapses of structures in the area. The kind of soil, the amount of clay and silt it contains, and the type of clay minerals in its composition exacerbate these problems. In addition, the research aims to reduce these problems and reduce environmental pollutants that negatively affect human health and reduce economic costs. Conducting a comprehensive study and a new management strategy is necessary to address the challenges related to shallow foundation collapses and reduce material losses. The main objective of the research is to develop a method to improve the geotechnical properties of soil in Al-Dair area. Field visits were conducted, and multiple soil samples were collected from different positions using a hand drill to a depth of 1.5 m. The results showed that soil samples treated with cement dust (C) at 2%, 4%, 6%, and 8% and ceramic dust (CD) at 5% and 10% showed significant changes. The addition of both ceramic dust and cement reduced the plastic limit, liquid limit, plasticity index, and optimum moisture content of clayey soils. Conversely, there were significant increases in compressive strength, California bearing ratio, and maximum dry density.
Keywords: Improvement Soil, Compressive Strength, Maximum Dry Density, Optimum Moisture Content